Pengembangan Media Pembelajaran Berbasis Aplikasi Android dalam Pembelajaran CNC di Kelas XII Teknik Pemesinan - Abdillah, Ahmad Haris; Atiqoh, Atiqoh; Karyono, Hari (LP. Ma'arif Janggan Magetan, 2023)
This research aims to develop effective and interactive Android application-based learning media for learning CNC (Computer Numerical Control) in class XII Machining Engineering. This research uses the ADDIE development method which involves preliminary studies, learning media development, and data obtained from validation results from media experts 78.00%, material experts 92.22% and design experts 95.00% and three trials were carried out on students, namely individual trials obtained percentages 90.55%, small group trials obtained a percentage of 90.27% and field trials obtained a percentage of 93.43% with very good criteria. The conclusion of this research shows that the development of Android application-based learning media in CNC learning has very good quality and is suitable for use in the learning process, can foster student learning motivation, the Android application developed is very interesting and easy to use as well as innovative and effective in helping students in CNC subjects in class XII Machining Engineering, Android applications can improve students' theoretical and practical skills in CNC subjects in class XII Machining Engineering.